Pemberdayaan Perempuan Melalui Penyuluhan Pencegahan Stunting di Kampung Mukim Singkir Yan Kedah Malaysia (Kolaborasi Pengabdian Internasional) - Juliana, Septa; Munir, Fitrisa; Ahmad, Zalinah (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This community service activity aims to increase women's knowledge and awareness in preventing stunting in Kampung Mukim Singkir Yan, Kedah, Malaysia. The method for implementing this service uses counseling, which includes planning, implementing and monitoring with Universiti Utara Malaysia partners. The instrument for evaluating this activity is a questionnaire, and is then analyzed descriptively. The results of this service show that women's knowledge and awareness regarding stunting prevention in Kampung Mukim Singkir Yan, Kedah, Malaysia has increased regarding understanding of stunting problems, the worse impacts of stunting, and stunting prevention.